Could Bet v 1 affect sensitization molecular pattern in children? - Tosca, Maria Angela; Silvestri, Michela; Pistorio, Angela; Olcese, Roberta; Del Barba, Paolo; Ciprandi, Giorgio (Acta Biomedica Atenei Parmensis, 2019)
Background: Allergy is characterized by allergen-specific IgE production. Molecular-based allergy diagnostic allows to define the precise sensitization profile. Bet v 1 is the major allergen of the PR-10 family. It has been reported that pan-allergens could affect the sensitization panel in adults. Objective: This study aimed to evaluate the impact of Bet v 1 sensitization on clinical presentation in a sample of children with Bet v 1-sensitization; oral allergy syndrome (OAS) or anaphylaxis (ANA) were considered. Methods: Serum IgE molecular components were assessed by ISAC method. Sera and clinical data from 132 children, 91 males (68.94%) and 41 females (31.06%), mean age 9.08 years (3.45 years), were analyzed. Results: Bet v 1-sensitized children were frequently, but not exclusively, sensitized to other molecules belonging to PR-10 family. However, there was no significant difference concerning IgE levels between children with or without food allergy and between children with OAS and ANA, but hazelnut only for generic food allergy. Conclusions: The present study demonstrates that Bet v 1 sensitization may affect the sensitization pattern in children living in Genoa, a Mediterranean city located in a birch-free area, but it is unable to discriminate patients from a clinical point of view. So, ISAC test should be integrated with more precise IgE assay.